การจัดการเรียนรู้จากงานของพ่อผ่านสะเต็มศึกษาเพื่อพัฒนาทักษะการแก้ปัญหาและประสบการณ์ การเรียนรู้วิศวกรรมศาสตร์ของเด็กปฐมวัย - เกียรติทวี, สิริญ์ลดาฌ์; ทองถาวร, รัชชุกาญจน์; อุปันโน, ไพบูลย์ (Journal of Education Studies, Chulalongkorn University, 2019)
The purposes of this research were 1) to design integrated learning units from the King’s projects through STEM education, 2) to study the problem-solving skills of early childhood children learned through STEM education, 3) to investigate the engineering experiences of early childhood children learned through STEM education. The target group in this research was seventeen K-3-students who were studying at Chairojsirin Kindergarten Chiangmai School. They were purposively selected. The instruments used for this study were 1) experiential learning plans of the King’s Projects through STEM education for developing kindergartner’s problem-solving skills as well as promoting their engineering experiences, 2) pictorial problem-solving skills assessment for early childhood children, and 3) pictorial engineering experience assessment for early childhood children. The data was analyzed by computing percentage and mean of the scores of the student’s problem-solving skills and engineering experiences, then compared it with the school’s criteria at 70.00%. The results found that: 1) There were three integrated units of the King’s Projects through STEM education; 2) The findings of the study in the problem-solving skills of the target group, learned through STEM education experiential learning plans, indicated that their average scores were at 84.41% which were higher than the school’s criteria at 70.00%; 3) The result of the study of the engineering experiences of the target group, learned through STEM education experiential learning plans, showed that their average scores were at 94.51% which were higher than the school’s criteria at 70.00%.